(untitled) (Existential Analysis: Journal of the Society for Existential Analysis, 2012)
This paper is based on my talk at SEA conference 2011 in London which was based on my book Meditation in The Age of Facebook and Twitter. Here, I explore a concept called transhumanist meditation and its implications for society. The discussion covers many existential principles which we could encounter as our relationship to the world changes fundamentally in a ’transhumanist’ world.